The Age of Rightly Guided Caliphs AL KHULAFA AR-RASHIDIN - Uthman ibn Affan History of Islam - Aziz, Maulana Abdul; Aziz, Maulana Abdul (Riyadh, Saudi Arabia Darussalam Publishers, 2012)
This book tells the life story of Uthman ibn Affan (RA), the third Caliph of Islam, in a clear and engaging style suitable for young readers. It begins with his early life as a wealthy and respected member of the Quraysh tribe in Makkah and his early acceptance of Islam through Abu Bakr (RA). The book highlights his strong faith, honesty, modesty, and generosity$1 (Bespecially during the time of the Prophet Muhammad (PBUH). Uthman (RA) is known for funding the Tabuk expedition and purchasing a well in Madinah for public use. As Caliph, Uthman (RA) made one of the most significant contributions to Islamic history: the compilation and standardization of the Qur$1 (Ban, which helped preserve it in its original form. The book also discusses the expansion of the Islamic empire into regions like North Africa and parts of Persia under his leadership. Toward the end, it addresses the internal conflicts and unrest that arose due to political challenges and accusations of nepotism. Despite his peaceful and kind nature, Uthman (RA) was martyred during a siege at his home while reading the Qur$1 (Ban. The book concludes by reflecting on his lasting legacy and his dedication to Islam, presenting him as a role model of patience, faith, and leadership.s
This book is part of the History of Islam series published by Darussalam, designed to present the lives of the Rightly Guided Caliphs in a simple and engaging way for young readers. Focused on the life and leadership of Caliph Uthman ibn Affan (RA), it highlights his contributions to Islam, including the compilation of the Qur'an, expansion of the Islamic empire, and his personal qualities such as generosity and piety. The book is written in easy English and aims to educate children and teenagers about important Islamic figures and historical events.
Keywords: The Age of Rightly Guided Caliphs AL KHULAFA AR-RASHIDIN - Uthman ibn Affan